Электрическая модель состояния гидратации пациента во время процедуры ультрафильтрации - Сокол, Евгений Иванович; Воинова, Марина Владимировна; Ткачук, Б. В.; Томашевский, Роман Сергеевич (НТУ "ХПИ", 2014)
В данной статье описаны вопросы контроля состояния гидратации пациента при гемодиализе. Обоснован выбор метода биоимпедансометрии (БИМ) для контроля водного статуса пациента. Описан принцип метода БИМ, а также недостатки существующей модели. Приведен обзор содержания жидкости в организме, а также распределение ее по секторам и перемещение между ними во время процедуры ультрафильтрации (УФ). Разработана новая электрическая модель, жидкостной части организма с разбиением на водные секторы. Также разработана модель с учетом динамики перемещения жидкости в организме при УФ.

This article describes the issues of control of the hydration state of the patient during procedures ultrafiltration and hemodialysis. The method of bioimpendancometry (BIM) for monitoring the water status of the patient has been chosen. The principle of the method of BIM are described. Also, the drawbacks of the existing equivalent circuit for bioimpedansometry are described. The overview of the content of body fluids, as well as its distribution across sectors are provided. The process of movement of fluid in patient body between interstitial and vascular sectors during procedure ultrafiltration are presented. The new equivalent circuit for BIM of the liquid portion of the body with sectorization has been developed. Also, equivalent circuit taking into account the dynamics of movement of body fluids during the procedure ultrafiltration has been developed. The mathematical description of proposed model is presented. The new criterion for end procedure ultrafiltration has been proposed.
Electrical model of the hydration state of the patient during the ultrafiltration
Keywords: гемодиализ; биоимпеданс; сухой вес; водный баланс; hemodialys; ultrafiltration; bioimpedans; dryweight; water balance